Irregular migration, climate change, and gender in Guatemala: Local perspectives - Penel, Charlotte; Madurga Lopez, Ignacio; Higuera Florez, Julian; Palou, Nohelia (2025)
This report explores the interrelations between irregular migration and the impacts of climate change from a gender perspective in Guatemala, drawing on knowledge-based evidence and local experiences. This research was motivated by the notable absence of a comprehensive study focused on Guatemala that integrates an intersectional gender approach to examine migration related to climate change.